Geology, particle size distribution and clay fraction mineralogy of selected vineyard soils in South Africa and the possible relationship with grapevine performance - Van Schoor, Lourens H. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2001.